STRATEGIC ANALYSIS AND COMPETITIVE POSITIONING OF PT NEYOKI LIMA BENUA - Shafa Sayyidina; Ratna Taliwarih; Yosephine Tiffany; Merliana Putri Wulandari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
The research investigates how PT Neyoki Lima Benua navigates strategic pressures in the customs brokerage and logistics sector in Indonesia, particularly the escalation of price competition and the fast pace of regulatory adjustments in import procedures. The study aims to clarify the company’s strategic orientation, assess its competitive position, and determine the extent to which its current practices reinforce long-term resilience. A qualitative method was applied through in-depth interviews, direct observation of operational activities, and a review of internal and external documents to capture the firm’s strategic posture. The distinct contribution of this work lies in its examination of a medium-scale logistics enterprise that integrates a full-service One-Stop Solution framework, an approach that receives limited attention in existing strategic management research within this industry. The analysis shows that the company employs a hybrid strategic model that balances cost efficiency with service differentiation, supported by a consolidation facility in China and a main office located close to Tanjung Priok Port. These conditions enhance operational effectiveness, elevate service precision, and reinforce the firm’s competitive stance. Several constraints remain, particularly the size of the workforce, the limited adoption of digital tools, and exposure to shifts in import regulations. The study highlights the need for systematic digital development, stronger collaborative networks, improved staff capabilities, and gradual expansion into new markets. Further studies may explore digital transformation in customs brokerage or conduct comparative reviews across similar firms to broaden the strategic implications.